Arachidonic Acid Induces the Migration of MDA-MB-231 Cells by Activating Raft-associated Leukotriene B4 Receptors - De Chatterjee, Atasi; Roy, Debarshi; Guevara, Priscilla; Pal, Rituraj; Narayan, Mahesh; Roychowdhury, Sukla; Das, Siddhartha (Clinical Cancer Drugs, 2018)
Background: The migration of tumor cells is critical in spreading cancers through the lymphatic nodes and circulatory systems. Although arachidonic acid (AA) and its soluble metabolites have been shown to induce the migration of breast and colon cancer cells, the mechanism by which it induces such migration has not been fully understood. Objective: The effect of AA on migratory responses of the MDA-MB-231 cell line (a triple-negative breast cancer cell) was examined and compared with MCF-7 (estrogen-receptor positive) breast cancer cells to elucidate the mechanism of AA-induced migration. Methods: Migrations of breast cancer cells were examined with the help of wound-healing assays. AA-induced eicosanoid synthesis was monitored by RP-HPLC. Cellular localizations of lipoxygenase and lipid rafts were assessed by immunoblot and confocal microscopy. Results: AA treatment stimulated the synthesis of leukotriene B4 (LTB4) and HETE-8, but lowered the levels of prostaglandin E2 (PGE2), prostaglandin D2 (PGD2), and HETE-5 in MDA-MB-231 cells. Further analysis indicated that AA increased the expression of 5-lipoxygenase (5-LOX) in this cell line and inhibiting its expression by small molecule inhibitors lowered the production of LTB4 and reduced migration. In contrast, MCF-7 cells did not show any appreciable changes in eicosanoid synthesis, 5-LOX expression, or cellular migration. Conclusion: Our results suggest that AA treatment activates the BLT1 receptor (present in membrane microdomains) and stimulates the synthesis of LTB4 production, which is likely to be associated with the migration of MDA-MB-231 cells.
Keywords: lipid rafts